2020
DOI: 10.1002/adma.202001093
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Manufacturing of Free‐Standing, Strong Ti3C2Tx MXene Films with Outstanding Conductivity

Abstract: Free‐standing films that display high strength and high electrical conductivity are critical for flexible electronics, such as electromagnetic interference (EMI) shielding coatings and current collectors for batteries and supercapacitors. 2D Ti3C2Tx flakes are ideal candidates for making conductive films due to their high strength and metallic conductivity. It is, however, challenging to transfer those outstanding properties of single MXene flakes to macroscale films as a result of the small flake size and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
552
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 720 publications
(598 citation statements)
references
References 55 publications
9
552
1
7
Order By: Relevance
“…[ 14,15 ] High electronic conductivity (up to 15 000 S cm −1 ), high packing density (up to 4 g cm −3 ), along with high pseudocapacitance endow Ti 3 C 2 T x ultrahigh volumetric capacitance (≈1500 F cm −3 ), which gives Ti 3 C 2 T x incomparable advantages over other electrode materials for supercapacitors. [ 16 ] However, Ti 3 C 2 T x electrodes suffer from long ion transport pathways due to the stacking nature of 2D materials, leading to ultra‐low rate performance in a thick electrode. When used as a power supply for electronic devices where high areal energy densities at high rates are required, MXene electrodes need to be thick enough to ensure high charge storage capability.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14,15 ] High electronic conductivity (up to 15 000 S cm −1 ), high packing density (up to 4 g cm −3 ), along with high pseudocapacitance endow Ti 3 C 2 T x ultrahigh volumetric capacitance (≈1500 F cm −3 ), which gives Ti 3 C 2 T x incomparable advantages over other electrode materials for supercapacitors. [ 16 ] However, Ti 3 C 2 T x electrodes suffer from long ion transport pathways due to the stacking nature of 2D materials, leading to ultra‐low rate performance in a thick electrode. When used as a power supply for electronic devices where high areal energy densities at high rates are required, MXene electrodes need to be thick enough to ensure high charge storage capability.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we found that microscopic silk‐MXene membranes remained conductive even if the content of silk matrix was estimated to be around 68% but silk shell having only 2.5 nm thickness (corresponding to 3–4 backbones) (Table S1, Supporting Information). Electrical resistance measurements were made using the four‐point‐probe technique [ 11 ] and the conductivity was calculated using thicknesses obtained via averaging measured thicknesses from SEM images (examples shown in Figure S14, Supporting Information). These measurements show a high conductivity for pristine MXene films of 10 5 –10 6 S m −1 comparable with those reported in literature (10 5 Sm −1 and above) (Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…2D functional materials such as graphene, transition metal dichalcogenides, and hexagonal boron nitride have garnered much interest in the scientific community due to their unique chemical, electrical, photonic, and structural properties as pure materials and as components of composites. [1][2][3][4][5][6][7][8] In recent years, a novel family of 2D materials known as MXenes [9,10] has become the subject of intense research due to their high electrical conductivity reaching higher than 15000 S cm −1 (Ti 3 C 2 ) [11] coupled with high Young's modulus values, 330 ± 30 GPa for Ti 3 C 2 [12] and 386 ± 13 GPa for Nb 4 C 3, [13] among solutionprocessed 2D materials. [12,14,15] Their rich surface chemis-bonding between chains such as β-sheets and random coils that determine the size of each block and also the ultimate mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…MXenes have superb metallic conductivity from 5000 to over 15 000 S cm −1 , [18,74] and have found applications in areas where superior electrical conductivity is considered pivotal. In this section, examples of the major applications necessitating the use of highly electrically conducting materials are discussed.…”
Section: Applications Of Mxenes As An Electrically Conductive Materialsmentioning
confidence: 99%
“…[31] These variables can modify the conductivity of a multilayered MXene disk from 1 S cm −1 to as high as 15 000 S cm −1 for a transparent and flexible MXene film. [18,32] Thus, while designing MXenes for applications that require a high electrical conductivity, careful control over the influencing factors is essential. For example, in a study performed by Shuck et al, the source material of Ti 3 C 2 T x MXene was found to influence the electrical conductivity of the resultant MXene.…”
Section: Introductionmentioning
confidence: 99%